ANALISIS SENSITIVITAS RESPON KONSUMEN PADA EKSTENSIFIKASI MEREK PEMBERSIH LANTAI MEREK SO KLIN - Lubis, Arlina Nurbaity; Rahmawati, Magdalena (BISMA: Jurnal Bisnis dan Manajemen, 2011)
The Objective of this research is to know and to examine the degree of consumer response sensitivity and direction on brand extension for So Klin floor cleaner. This research used the descriptive method, method of sensitivity response and statistical methods, namely validity test and reliability test. The results of examination showed that sensitivity consumer response for brand extension from So Klin detergent to So Klin floor cleaner was 1.04 which included in sensitive category. The stimuli has changed due to brand extension from So Klin detergent to So Klin floor cleaner. Based on product attribute and phase from hierarchical effect, it showed that there were a positive score of 35. This positive sign meant that the stimuli from So Klin floor cleaner had a higher consumer response.